"No Girls on the Internet": The Experience of Female Gamers in the Masculine Space of Violent Gaming - Carina Assunção (Press Start, 2016)
The experience of female gamers in the masculine space of violent videogame playing was explored. Hypotheses concerned identity management strategies used online as well as offline. The study adopts a mixed methods approach. 291 women aged 18-48 were recruited via advertisements on social media. An online questionnaire addressed gaming habits, while a focus group with three women explored the pleasures they take from playing violent games. It was found that those who do play violent games, play video games for significantly more hours than those who don't play games which are violent. In turn, the more hours they play, the more likely it is they will discuss their gamer identity socially. Focus group findings however, showed that, by default, women players stay away from the topic of gaming. Regarding their gaming habits, the results support previous research that choice of games depend on the time gamers have available. Investigating female gamers’ reactions to harassment based on their gender identity during online gaming, it was found that those exposed to toxic behaviour probably stopped playing online because of its impact on their psychological well-being. Additionally, the focus group showed participants strategically express their gender identity when they have won. The impact for women to succeed in a male-dominated activity is discussed.